1994
DOI: 10.1111/j.1472-765x.1994.tb00931.x
|View full text |Cite
|
Sign up to set email alerts
|

A new cell assay to determine the virulence of Francisella tularensis

Abstract: A cell culture assay to determine the virulence of Francisella tularensis was devised. Murine cell lines P388 and J774 were significantly more susceptible to F. tularensis Schu4 than the attenuated live vaccine strain. The ability of F. tularensis strains to cause cell death correlated with their virulence to mice. Use of this assay with infected cells separated from susceptible uninfected cells by a membrane with 0.1 μm pores, failed to demonstrate possible diffusible exotoxins produced by F. tularensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Here, the parameters are estimated in four stages ( §2.2), starting with the birth rate. The reciprocal of this is estimated through the median time until cell death-found to be 41.2 h. The magnitude of this duration is supported by the only other similar in vitro study that could be found [53], in which at 24 h 100% of cells are still healthy (cf. 92% in [28]).…”
Section: Parametrizationmentioning
confidence: 67%
See 1 more Smart Citation
“…Here, the parameters are estimated in four stages ( §2.2), starting with the birth rate. The reciprocal of this is estimated through the median time until cell death-found to be 41.2 h. The magnitude of this duration is supported by the only other similar in vitro study that could be found [53], in which at 24 h 100% of cells are still healthy (cf. 92% in [28]).…”
Section: Parametrizationmentioning
confidence: 67%
“…92% in [28]). Pooling data from other, related studies is not undertaken, because the timing of cell degradation is dependent on a number of factors, such as the strain [28,34], host species [53] and route of infection [19].…”
Section: Parametrizationmentioning
confidence: 99%
“…We expected a slightly different value for this parameter due to different extrapolation techniques from Lindemann et al (2011) . The reciprocal of the birth rate λ is estimated through the median time until cell death-found to be 43.4 h. This duration is supported by another similar in vitro study ( Mack et al, 1994 ), in which at 24 h 100% of cells are still healthy (92% in Lindemann et al (2011) ).…”
Section: The Parametrisation Of Our Francisella Tularensis mentioning
confidence: 66%
“…After 8 hours the vast majority of bacteria are located within the cytosol [10,12,15,18-20]. Work by Mack and colleagues [21] as well as Edwards and colleagues [22] has demonstrated, through direct comparisons, that F. tularensis infections show an essentially identical disease progression in J774A.1 cells as P388D1 cells, the murine macrophage line used in this study.…”
Section: Resultsmentioning
confidence: 99%